Precarious employment and precarious life: youth and work in Pretoria's white working-class suburbs. (2nd September 2021) - Pieterse, Jimmy; Sharp, John
ABSTRACT: Many Afrikaans-speaking people in Pretoria's white working-class suburbs during the apartheid era lost their jobs in the 1990s when the heavy industries in which they worked were downsized or closed down. This paper explores the livelihood strategies open to the next generation – the ex-workers' children who are confronted by wage employment opportunities very different from those open to their parents. Popular interpretations of the position of members of the apartheid-era white working class in South Africa today are contradictory. One narrative holds that their present circumstances mark the return of the "Poor Whites" of the early twentieth century, while a second contends that they continue to benefit uniformly from the "wages of whiteness." The evidence we draw from our ethnographic field research in the former white working-class suburbs suggests that both of these understandings simplify a complex situation. We show the ways in which young people endeavour to fashion livelihoods at present, and discuss how the differences between their various livelihood strategies shape their understanding of what it means to be Afrikaans and white in the post-apartheid era.